3D surface imaging of abdominal wall muscular contraction. (July 2019) - Todros, Silvia; de Cesare, Niccolò; Pianigiani, Silvia; Concheri, Gianmaria; Savio, Gianpaolo; Natali, Arturo N.; Pavan, Piero G.
Highlights: 3D laser scanning is an accurate and reliable method to evaluate surface shape variations. A significant difference between relaxed and contracted abdominal wall surfaces is found. Muscle activation causes raising of linea alba and rectus muscles and lowering of lateral muscles. Displacements reach a maximum value of 12.5 mm. Abstract: Background and Objective: The biomechanical analysis of the abdominal wall should take into account muscle activation and related phenomena, such as intra-abdominal pressure variation and abdomen surface deformation. The geometry of abdominal surface and its deformation during contraction have not been extensively characterized, while represent a key issue to be investigated. Methods: In this work, the antero-lateral abdominal wall surface of ten healthy volunteers in supine position is acquired via laser scanning in relaxed conditions and during abdominal muscles contraction, repeating each acquisition six times. The average relaxed and contracted abdominal surfaces are compared for each subject and displacements measured. Results: Muscular activation induces raising in the region adjacent to linea alba along the posterior-anterior direction and a simultaneous lowering along lateral-medial direction of the abdominal wall sides. Displacements reach a maximum value of 12.5 mm for the involved subjects. The coefficient of variation associated to the abdomen surface measurements in the same configuration (relaxed or contracted) is below 0.75%. Non-parametric Mann-Whitney U test highlights that the differences between relaxed and contracted abdominal wall surfaces are significant ( p < 0.01). Conclusions: Laser scanning is an accurate and reliable method to evaluate surface changes on the abdominal wall during muscular contraction. The results of this experimental activity can be useful to validate numerical models aimed at describing abdominal wall biomechanics.